Urban forests and pollution mitigation: Analyzing ecosystem services and disservices (2011)
The purpose of this paper is to integrate the concepts of ecosystem services and disservices when assessing the efficacy of using urban forests for mitigating pollution. A brief review of the literature identifies some pollution mitigation ecosystem services provided by urban forests. Existing ecosystem services definitions and typologies from the economics and ecological literature are adapted and applied to urban forest management and the concepts of ecosystem disservices from natural and semi-natural systems are discussed. Examples of the urban forest ecosystem services of air quality and carbon dioxide sequestration are used to illustrate issues associated with assessing their efficacy in mitigating urban pollution. Development of urban forest management alternatives that mitigate pollution should consider scale, contexts, heterogeneity, management intensities and other social and economic co-benefits, tradeoffs, and costs affecting stakeholders and urban sustainability goals.